The Plant-Transpiration Response to Vapor Pressure Deficit (VPD) in Durum Wheat Is Associated With Differential Yield Performance and Specific Expression of Genes Involved in Primary Metabolism and Water Transport - Medina, Susan; Vicente, Rubén; Nieto-Taladriz, Maria Teresa; Aparicio, Nieves; Chairi, Fadia; Vergara-Diaz, Omar; Araus, José Luis (Frontiers in Plant Science, 2019)
The regulation of plant transpiration was proposed as a key factor affecting transpiration efficiency and agronomical adaption of wheat to water-limited Mediterranean environments. However, to date no studies related this trait to the performance in field. In this study, the transpiration response to increasing vapour pressure deficit (VPD) of 20 modern semi-dwarf durum wheat Spanish cultivars was evaluated under controlled conditions, and evaluated in field from water stressed to good agronomical conditions in the Mediterranean,. A group of linear-transpiration (LTR) lines to plant transpiration exhibited better performance in grain yield and biomass compared to the segmented-transpiration (STR) lines, particularly in the wetter environments, opposite occurred only in the most stressed trial. LTR lines generally exhibited better water status (stomatal conductance) and larger green biomass (vegetation indices) during reproductive stage than R lines. In both groups, the responses to growing conditions were associated with the expression levels of dehydration-responsive transcription factors (DREB) leading to different performances of primary metabolism-related enzymes. Thus, the response of LTR under fair to good conditions was associated with higher transcription of genes involved in nitrogen (GS1 and GOGAT) and carbon (Rubisco large subunit) metabolism, also water transport (TIP1.1). In conclusion, modern durum wheat lines differed in their response to water loss, segmented transpiration seemed to favour uptake and transport of water and nutrients, and photosynthetic gas exchange leading higher grain yield except for very harsh drought conditions. The transpiration response to VPD may be a trait to further explore when selecting adaptation to specific water conditions.